Whole blood transfusion versus component therapy in trauma resuscitation: a systematic review and meta‐analysis - Ellen Crowe; Stacia M. DeSantis; Austin Bonnette; Jan O. Jansen; Jose‐Miguel Yamal; John B. Holcomb; Claudia Pedroza; John A. Harvin; Marisa B. Marques; Elenir B.C. Avritscher; Henry E. Wang (Journal of the American College of Emergency Physicians Open, 2020)
Abstract Background Patients with hemorrhagic shock from trauma often require balanced blood product transfusion with red blood cells, plasma, and platelets. Resuscitation with whole blood resuscitation is becoming a common practice. We performed a systematic review and meta‐analysis of studies comparing whole blood transfusion with balanced component therapy in patients suffering from traumatic hemorrhagic shock. Methods We searched MEDLINE Ovid, EMBASE, and the Cochrane Library for human studies comparing whole blood with component blood therapy published from January 2007 to June 2019. We included studies from both civilian and military settings and that reported 24‐hour, in‐hospital, or 30‐day mortality. We followed the Preferred Reporting Items in Systematic Reviews and Meta‐Analyses (PRISMA) guidelines, assessing study quality, publication bias, and heterogeneity. We used meta‐analytic models to determine the associations (odds ratio [OR] with 95% confidence interval [CI]) between whole blood transfusion and (1) 24‐hour mortality, and (2) in‐hospital or 30‐day mortality. Results A total of 1759 identified studies, 12 (reporting on n = 8431 patients) met inclusion criteria. There was heterogeneity in the design, setting, interventions, and outcomes of the studies. On meta‐analysis, whole blood transfusion was not associated with 24‐hour mortality (OR = 0.83; 95% CI = 0.56–1.24) or in‐hospital/30‐day mortality (OR = 0.79; 95% CI = 0.48–1.31). Conclusion In this systematic review and meta‐analysis, compared with conventional component transfusion, whole blood was not associated with 24‐hour or in‐hospital mortality. However, there were important limitations with and heterogeneity among the primary studies. Additional study is needed to determine the effectiveness of whole blood.